1969
DOI: 10.12669/pjms.301.4194
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Abh Secretors and Non Secretors in Pakistani Population

Abstract: Objective: ABO blood group and secretor status is valuable in relation to some diseases in clinical and forensic medicine. Across the globe there are geographic and racial differences in the frequency of secretors and non-secretors. Aim of this study was to evaluate the status of ABH blood group secretors and non-secretors in Karachi (Pakistan). Methods: Blood and saliva samples were randomly collected from one hundred and one (n=101) healthy adult students (76 male, 25 female) ranging in age from 15 to 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 1 publication
5
13
0
Order By: Relevance
“…Emeribe et al [11] and Jaff [12] reported similar findings in their studies. Saboor M et al, [13] conducted a study to evaluate the ABH blood group among 101 healthy adult students and concluded that the frequency was highest in blood group B which was in accordance with our study. It is also seen that out of 50 subjects, 48 of them showed the secretor level similar to the study conducted by Pereira M et al, [14] Kimura A et al, [15] Parekh P et al, [16] and Pawan Motghare et al [4] .…”
Section: Discussionsupporting
confidence: 91%
“…Emeribe et al [11] and Jaff [12] reported similar findings in their studies. Saboor M et al, [13] conducted a study to evaluate the ABH blood group among 101 healthy adult students and concluded that the frequency was highest in blood group B which was in accordance with our study. It is also seen that out of 50 subjects, 48 of them showed the secretor level similar to the study conducted by Pereira M et al, [14] Kimura A et al, [15] Parekh P et al, [16] and Pawan Motghare et al [4] .…”
Section: Discussionsupporting
confidence: 91%
“…Lewis blood type is genetically determined by the Lewis gene ( fucosyltransferase 3 ), which encodes for α1,3/4 fucosyltransferase, and the Secretor gene ( fucosyltransferase 2 ), which encodes for α1,2 fucosyltransferase [ 8 ]. Worldwide it is estimated that around 20% of individuals have inactive secretor genes (non-secretor) though geographic and racial differences have been reported [ 9 , 10 ]. The breast milk of non-secretor mothers lack α1,2 fucosyl-oligosaccharides [ 7 , 11 ] and contain around half of the amount of neutral oligosaccharides compared to the breast milk of mothers with active Secretor genes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of which 75% were of group O and 61.5% in group A [Table/ Fig-3]. These two studies compared Absorption-Inhibition and Absorption-Elution Methods in the detection of ABO (H) antigens in vaginal samples, submitted in sexual offense cases and stated that the Absorption-inhibition is a well-established method for the identification of ABO (H) antigens [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent study done in 2014 by Saboor M et al, to evaluate the ABH blood group among 101 healthy adult students (76 male, 25 female ranging in age from 15 to 40 years), to know the secretors and non-secretors in people of Karachi, Pakistan using haemagglutination inhibition method of saliva [14]. They concluded that frequency of ABH secretor is high (64.4%).…”
Section: Discussionmentioning
confidence: 99%